Floristic analysis of weed flora in vegetable under organic production - Živković, Sanja (Acta herbologica, 2024)
The analysis of the weed flora in the vegetable in the village of Trmčare revealed the presence of a total of 44 weed species [23 weed, 19 weed-ruderal, 1 ruderal and 1 weed of meadows and pastures]. The recorded weed flora is dominated by representatives of the class Magnoliopsida (dicotyledons, broad-leaved weeds) with 38 species, while only six species are present from the class Liliopsida (monocotyledons, narrow-leaved weeds). The analysis of weed life forms in raspberry plantations shows a dominance of therophytes (70,45%) compared to geophytes (13,64%), while hemicrypthophytes (11,36%) and thero-hemicrypthophytes only 4,55%. The number of weeds was not high, because inter-row cultivation was done every ten to fifteen days, and weeds were manually removed in the rows, around the plants. Regardless of the mechanical removal of weeds, the diversity of the weed flora was not negligible. In all observed vegetable under organic production, the most frequent winter weeds were: Camelina sativa (L.) Crantz., Poa annua L., Myosotis arvensis (L.) Hill., Veronica persica Poir., Cerastium glomeratum Thuill., Lamium purpureum L. From early spring weeds the most frequent were present Chenopodium polyspermum L., Polygonum lapathifolium L., Polygonum persicaria L., Polygonum convolvulus L, Galium aparine L., and of the late spring weeds were most often present Chenopodium album L., Amaranthus retroflexus L., Amaranthus hybridus L., Setaria viridis (L.) P. B., Hibiscus trionum L., Portulaca oleracea L. Key words: vegetable, organic production, weed flora, broad-leaved weeds, narrow-leaved weeds